Impact of Nurse Roster Management on Nurses’ Job Satisfaction in a Tertiary Care Hospital Lahore, Pakistan - Fauzia Batool, Maria Ali, Tahira Aslam, Razia Kousar, Ayesha Talib, Hina Aslam (Pakistan Journal of Medical & Health Sciences, 2023)
Roster management is seen to be an essential component of Health care settings. Rostering for hospital staff in general and nurses in particular is challenging because of variety of issues and demands in many shifts and days. Job satisfaction of nurses is an indicator of the services provided in a specific healthcare facility. Roster management and job satisfaction are very much dependent on each other although roster management is a complex task. Objectives: The study objective was to identify the impact of nurse roster management on nurses’ job satisfaction in a Tertiary Care Hospital Lahore, Pakistan. Methods: A cross-sectional study was conducted at The University of Lahore teaching Hospital, Lahore Pakistan. A non-probability convenient sampling technique was used with a sample size of 133 nurses working in the hospital were included. In this study, Mines Job Satisfaction Scale (MJSS) was used for nurses’ job satisfaction level and implementation of nurse roster management questionnaire was used for data collection. The following methods were used to analyze the data: double linear regression, one-way analysis of variance (ANOVA), Pearson correlation, and independent t test. Results: The findings showed that there was a significant association between the nurse roster management with all management functions on nurses job satisfaction level (p=.0002-.012). The two functions of management which affect the nurse job satisfaction level was organizing and controlling. Conclusions: Researchers determined that the roster management of nurses statistically correlated with the job satisfaction level of nurses. Nursing supervisors should have the competence to improve the job satisfaction level of nurses by optimizing the roster management especially on organizing and controlling aspect. Keywords: Nurses; Roaster management; Job Satisfaction; Health Care Settings; Nursing Supervisors; Turnover; Absenteeism